Kontribusi Nilai Ekonomi Kayu Manis Sebagai Hasil Hutan Bukan Kayu Di Kabupaten Gayo Lues - Andi Fauzan R Pohan; Nurhasanah Hasbi; Anshari Anshari; Astri Winda Siregar (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Cinnamon as a non-timber forest product plays a significant economic role in supporting rural livelihoods in Gayo Lues Regency, Aceh Province. This study analyzes the economic value contribution of cinnamon cultivated and utilized by communities in several villages of Kutapanjang District. The primary product utilized is cinnamon bark, while the stem is not commercially traded and is instead used as household fuelwood. The findings indicate that the average annual income derived from cinnamon bark reaches Rp26,557,283 per household, contributing 71% to total household income. In comparison, secondary livelihood activities contribute Rp2,213,106 or 29%. These results demonstrate that cinnamon functions as the dominant income source within the local agroforestry system. The aggregate economic structure reflects relatively stable returns, indicating resilience against short-term market fluctuations. The integration of household-based forest resource management and local economic activities highlights cinnamon’s strategic role in strengthening village economies. Therefore, cinnamon as a non-timber forest product represents a sustainable economic driver that supports rural development and forest-based livelihood systems in Gayo Lues Regency.